2022
DOI: 10.1007/s10980-022-01425-9
|View full text |Cite
|
Sign up to set email alerts
|

Forest water use is increasingly decoupled from water availability even during severe drought

Abstract: Context: Key to understanding forest water balances is the role of tree species regulating evapotranspiration (ET), but the synergistic impact of forest species composition, topography, and water availability on ET and how this shapes drought sensitivity across the landscape remains unclear.Objectives: Our aims were to quantify (1) the effect of forest composition and topography including elevation and hillslope gradients on the relationship between ET and water availability, and (2) whether the relationship h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
(47 reference statements)
0
5
3
1
Order By: Relevance
“…The contrasting results of our study with McQuillan et al. (2022) highlight the importance of local and regional factors in determining hydrologic response to drought.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The contrasting results of our study with McQuillan et al. (2022) highlight the importance of local and regional factors in determining hydrologic response to drought.…”
Section: Discussioncontrasting
confidence: 99%
“…However, for Walshes Creek we also concluded that reductions in downslope water subsidies can strongly affect locations that are accustomed to receiving them (hence the reduction in midslope LAI in Figure 6a2), although the drought was not severe enough to induce substantial water limitation in our simulated riparian zone. The contrasting results of our study with McQuillan et al (2022) highlight the importance of local and regional factors in determining hydrologic response to drought.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…A proteção do solo em florestas ripárias é um serviço importante para reduzir o assoreamento de corpos hídricos (Tambosi et al, 2015). E, apesar da proteção do solo através do dossel florestal ser importante para redução do fluxo de sedimentos também em posições superiores no relevo (Bacellar, 2005;Li et al, 2019), ao diminuir o fluxo, diminui-se também a quantidade de água que percorre e abastece os trechos mais inferiores do relevo, o que poderia impactar a provisão de água (Garcia, 2018;McQuillan et al, 2022). Desta forma, as diferenças encontradas são positivas, à medida que a menor proteção do solo na posição superior garante o abastecimento de água para as posições mais inferiores do relevo, e que a maior proteção do solo na posição inferior garante a maior proteção dos corpos hídricos.…”
Section: Serviços Hidrológicos Em Uma Floresta Secundária Em Duas Pos...unclassified